Loneliness Modulates Automatic Attention to Warm and Competent Faces: Preliminary Evidence From an Eye-Tracking Study - Saito, Toshiki; Motoki, Kosuke; Nouchi, Rui; Kawashima, Ryuta; Sugiura, Motoaki (Frontiers in Psychology, 2020)
Social connections are essential for human survival. Loneliness is a motivational factor for building and maintaining social connections. Automatic attention occurs with little cognitive effort and plays a key role in detecting biologically salient events, such as human faces. Although previous studies have investigated the effect of loneliness on social behavior, the effect of loneliness on automatic attention to human faces remains largely unknown. The present study investigated the effects of loneliness on automatic visual attention to warmth and competence facial information, which determines facial attraction. This study included 43 participants who rated warmth and competence facial information. Then, they engaged with the target-distractor paradigm in which they saw two house images at the top and bottom and indicated whether the images were identical. During the task, we presented two faces as distractors and measured visual attention toward the faces as automatic attention because participants did not have to attend to the faces. The results showed an interactive effect between subjective loneliness and facial information on automatic attention. Warm targets automatically captured the attention of people feeling relatively lonely, whereas competent targets automatically captured the attention of those who felt less lonely. These results suggest that loneliness adaptively influences automatic processing of social information.